The Potential of Beber Satay as a Culinary Tourism Attraction in Beber Village, Cirebon Regency - Ana Listiana; Eri Susanti; Fitriyani; Kurbaniatin; Lilis Andalasari (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2024)
Talking about culinary tourism in Indonesia, of course there are many kinds. Each region must have culinary specialties that make it a culinary tourist attraction, for example, the satay culinary. In Indonesia, there are many areas that are famous for satay culinary, one of which is Beber satay. This research is a descriptive qualitative study which aims to determine the potential of Beber satay as a culinary tourism attraction. The data collection methods used were observation, interviews, and documentation. The results showed that Beber satay can be said to have the potential to be developed and used as a culinary tourism attraction in Beber Village. Satay is very suitable as a mainstay menu to be served to visiting tourists.